THE EFFECT OF WORK DISCIPLINE, WORK MOTIVATION AND JOB SATISFACTION ON EMPLOYEE PERFOMENCE AT THE CLASS II IMMIGRATION OFFICE IN LHOKSEUMAWE - Ayu Nadila; Em Yusuf Iis; Marbawi; Nurmala (RADJA PUBLIKA, 2025)
This study aims to examine the influence of work discipline, work motivation, and job satisfaction on employee performance at the Class II Immigration Office in Lhokseumawe. The research method used is quantitative with an associative approach. Data were collected through questionnaires distributed to 48 employees as the research sample using a saturated sampling technique. The research instruments were tested with validity and reliability tests, while the classical assumption tests included normality, multicollinearity, and heteroscedasticity tests. Data analysis was carried out using multiple linear regression with the help of SPSS version 26. The results show that work discipline, work motivation, and job satisfaction have a positive and significant effect on employee performance, both partially and simultaneously. The coefficient of determination (R²) of 0.885 indicates that 88,5% of the variation in employee performance can be explained by the independent variables, while the remaining 88,5% is influenced by other factors not included in this study.